Current arrangements for teaching medical ethics to undergraduate medical students. - Bicknell, D J (1985)
Those teachers in contact with medical students from pre-clinical days onwards will impart their ethical views by example and by precept, but such learning by 'osmosis' is insufficient. There is a knowledge base to be imparted which will enrich the understanding of ethical judgements on clinical problems seen during the undergraduate years. However, the learning process continues after qualification and in particular the doctor's capacity to make ethical clinical judgements will evolve with maturity and experience. It is essential therefore that students see their teachers willing and able to debate ethical issues at the postgraduate level.